Um estudo comparativo de aptâmeros de ssRNA e ssDNA para a teranóstica do câncer de próstata - Lorenti, Sabrina (2024)
The ssRNA aptamers A6 and A11 exhibit high specificity for prostate cancer (CaP) tumor cells, particularly the PC-3 cell line. However, their clinical application is limited by instability and side effects. This study aims to develop modified ssDNA aptamers (LN-A6 and LN-A11) with enhanced stability and therapeutic potential. The ssRNA aptamers A6 and A11 were modified in silico to generate ssDNA aptamers (LN-A6 and LN-A11) that naturally resist degradation by RNases due to the absence of the 2' hydroxyl group. The structural similarity between the original (ssRNA) and modified (ssDNA) aptamers was visually analyzed, and molecular dynamics (MD) simulations were conducted for 100 ns at two different temperatures, 300K and 310K. The stability of the complexes during dynamics was assessed through the internal number of hydrogen bonds (H-bond) and root mean square deviation (RMSD) of the structures throughout the simulations. Additionally, the affinity and binding strength of the aptamers to PC-3 cells were measured by dissociation constant (KD) analysis using flow cytometry at different concentrations. The results demonstrate that the modification from ssRNA to ssDNA aptamers resulted in molecules with high structural similarity, greater affinity and binding strength to PC-3 cells, and increased stability. LN-A6 stands out as a promising candidate for future research aimed at developing innovative diagnostic and therapeutic tools for CaP.